2012
DOI: 10.1371/journal.pone.0051259
|View full text |Cite
|
Sign up to set email alerts
|

GTSE1 Is a Microtubule Plus-End Tracking Protein That Regulates EB1-Dependent Cell Migration

Abstract: The regulation of cell migration is a highly complex process that is often compromised when cancer cells become metastatic. The microtubule cytoskeleton is necessary for cell migration, but how microtubules and microtubule-associated proteins regulate multiple pathways promoting cell migration remains unclear. Microtubule plus-end binding proteins (+TIPs) are emerging as important players in many cellular functions, including cell migration. Here we identify a +TIP, GTSE1, that promotes cell migration. GTSE1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(111 citation statements)
references
References 72 publications
10
100
1
Order By: Relevance
“…Migration and invasion are important features controlling the metastasis of cancer cells, and these processes require changes to the microtubule cytoskeleton. In breast cancer, alteration of GTSE1 expression is associated with increased invasive potential, and GTSE1 was identified as a microtubule‐associated plus‐end tracking protein, which promotes cell migration through interactions with EB1 . Consistently, we have shown that migration and invasion of AM cells were stimulated by GTSE1 overexpression and suppressed by its depletion.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Migration and invasion are important features controlling the metastasis of cancer cells, and these processes require changes to the microtubule cytoskeleton. In breast cancer, alteration of GTSE1 expression is associated with increased invasive potential, and GTSE1 was identified as a microtubule‐associated plus‐end tracking protein, which promotes cell migration through interactions with EB1 . Consistently, we have shown that migration and invasion of AM cells were stimulated by GTSE1 overexpression and suppressed by its depletion.…”
Section: Discussionsupporting
confidence: 73%
“…Negative regulation of p53 allows cells to resist apoptosis and transition through the G2/M checkpoint, leading to tumor progression. In interphase, GTSE1 accumulates at growing microtubule plus‐ends by interacting with microtubule‐associated protein RP/EB family member 1 (EB1), and its activity is required for cell migration and focal adhesion formation . GTSE1 has been found to play roles in human cancer proliferation, apoptosis, and migration.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, EB1 appeared to be a more reliable marker as we found a strong correlation between EB1 accumulation at MT (+) ends and the inhibition of endothelial migration by VFL at all effective concentrations. These results are strengthened by recent works demonstrating that EB1 down-regulation impairs migration [35] and capillary-like tube formation in endothelial cells [36]. Taken together these observations make EB1 comets a crucial marker of cell migration and a potential target in neoangiogenesis.…”
Section: Discussionsupporting
confidence: 61%
“…GTSE1 is a microtubule plus-end tracking protein (ϩTIP) that binds directly to the microtubules. Its depletion results in disorganized microtubules (52). SENP3 is a SUMO isopeptidase that during mitosis interacts with Borealin, a chromosomal passenger complex protein involved in regulating chromosome congression, the SAC, and cytokinesis (53).…”
Section: Discussionmentioning
confidence: 99%